Response of sagebrush carbon metabolism to experimental precipitation pulses. (December 2016) - Mitra, Bhaskar; Mackay, D. Scott; Ewers, Brent E.; Pendall, Elise
Abstract: Effects of future large summer storm events due to climate change on vegetation carbon metabolism across western United States remains poorly understood. Canopy carbon metabolism of sagebrush ( Artemisia tridentata ) was evaluated for 7 days during the two driest months (July and August) by irrigating sagebrush plots with 20 mm precipitation pulses. Due to its dimorphic rooting system, we hypothesized sustained response to large precipitation events. Photosynthesis ( A n ) and stomatal conductance ( g s ) peaked within 2–3 days of irrigation and returned to pre-irrigation values by day 7. Predawn water potential ( Ψ pd ) peaked within 1 day and returned to its pre-pulse value by day 3 while potential quantum efficiency for light adapted leaves (F v ' / F m ' ) as well as intrinsic water use efficiency ( WUE i ) was unresponsive. Unlike leaves, fine roots in the top 30 cm of soil were not a carbon sink. Heterotrophic respiration ( R h ) was the dominant contributor to total soil respiration ( R s ), and peaked within 24 h before it dropped to pre-pulse value by day 3. Different environmental drivers regulated R s and R h, highlighting different kinetics of carbon production. Our study suggests ephemeral response of cold desert vegetation to future large summer storm events with important implications for the overall carbon storage capacity. Highlights: Response of sagebrush carbon metabolism to precipitation remains poorly understood. Photosynthesis peaked within 2–3 days of irrigation and returned to pre-irrigation values by day 7. Heterotrophic respiration ( R h ) was the dominant contributor to total soil respiration ( R s ). Fine roots at shallow soil layer were not a carbon sink.